Development of an improved device to control flame brightness in combustion chambers of steam boilers - Melnik, Olga; Parkhomenko, Roman; Shchokina, Olga; Aniskov Оlexandr; Tsibulevsky, Yuri; Kharitonov, Alexander; Omelchenko, Aleksandr; Chorna, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2017)
The study has helped create a device by developing the design of a sensor to control the fire brightness of a coal burner as well as by using the electronic circuit of an information processing unit. The proposed optical fiber transformer design provides a comparison of the brightness of adjacent areas and the total area of a separate torch, and it increases the viewing angle of the sensor up to 20 degrees. A third channel has been introduced to correct measurements, taking into account the radiation of combustion products that hinder the accuracy of the measurement. The study has determined the radiation spectrum of combustion products in the furnace and their dependence on the temperature of the flame. It has been revealed that the developed optical fiber sensor increases the area of the controlled flame, which increases the accuracy of control. The presence of a “window” in the logic source block will help adapt the device to the temperature and location of burners in the furnace. The design of the optical fiber transformer and some nodes of the electronic unit can be used in the development of serial combustion control devices for coal burners. The use of CCD matrices will help achieve future two-coordinate control of the burner flame and increase the selectivity and performance of the device